A Kinetic Sculpture Intervention for Individuals Grieving the Deaths of Family Members. Issue 1 (2nd January 2017) - Brandon, Kären E.; Goldberg, Rebecca M.
ABSTRACT: This article presents a creative intervention called kinetic sculpture for loss adaptation in grief counseling. This intervention is supported by professional literature regarding Bowenian family systems and creativity in counseling. The deaths of family members may generate much uncertainty for clients regarding functioning of their family systems. Kinetic sculpture allows clients to create visual examples of family equilibrium before, in the midst of, and after the deaths of family members. Insight gained from engaging in this intervention can aid clients in making aspirational plans for their own adaptations to loss. In this article, we present step-by-step instructions for creating the kinetic sculpture, make recommendations for process questions to accompany the intervention, and apply the kinetic sculpture in a case example.